Solomon Islands : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Solomon Islands. (IMF Staff Country Reports; Country Report ;, 2020)
This 2019 Article IV Consultation with the Solomon Islands highlights that the country has made substantial progress since the Tensions in the early 2000s but faces considerable economic and governance challenges and is highly vulnerable to natural disasters. Finding new sources of growth is becoming urgent with the decline in logging. The consultation focused on similar issues to last year-restoring fiscal buffers to build resilience, strengthening public financial management and public investment management, setting a medium-term fiscal strategy, improving governance, improving exchange rate management and building conditions for sustainable growth. The report recommends developing a holistic approach to medium-term fiscal policy by setting a realistic spending envelope and establishing a medium-term revenue strategy. Together with strengthened budget planning and expenditure control, this would provide greater budget predictability and support natural disaster contingency planning. It is also imperative to strengthen enforcement of governance standards, apply the mining fiscal regime rigorously, improve transparency and advance the anti-corruption agenda.